2009
DOI: 10.1128/iai.00361-09
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiiCyclophilin 18-Mediated Production of Nitric Oxide Induces Bradyzoite Conversion in a CCR5-Dependent Manner

Abstract: Toxoplasma gondii modulates pro-and anti-inflammatory responses to regulate parasite multiplication and host survival. Pressure from the immune response causes the conversion of tachyzoites into slowly dividing bradyzoites. The regulatory mechanisms involved in this switch are poorly understood. The aim of this study was to investigate the immunomodulatory role of T. gondii cyclophilin 18 (TgCyp18) in macrophages and the consequences of the cellular responses on the conversion machinery. Recombinant TgCyp18 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 66 publications
0
51
0
Order By: Relevance
“…In contrast, no significant proliferative response was demonstrated after stimulation with 25 150 ) of the TgCyp18 region abrogated this effect. This observation provides further evidence that TgCyp18 binding to CCR5 is antagonistic for spleen cell proliferation, but further study will be required to confirm this.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, no significant proliferative response was demonstrated after stimulation with 25 150 ) of the TgCyp18 region abrogated this effect. This observation provides further evidence that TgCyp18 binding to CCR5 is antagonistic for spleen cell proliferation, but further study will be required to confirm this.…”
Section: Discussionmentioning
confidence: 89%
“…TgCyp18 has been shown to stimulate macrophages to produce IL-12 and NO in a CCR5-dependent manner (25). However, the dose-dependent effect of TgCyp18 has not yet been elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many studies have shown that nitric oxide (NO) triggers the conversion between tachyzoite to bradyzoite forms and has parasiticidal effects. In addition to its immunoregulatory functions (Sibley et al, 1991;Candolfi et al, 1994;Bohne et al, 1994;Hayashi et al, 1996;Ibrahim et al, 2009), NO has immunopathological effects (Khan et al, 1997;Hayashi et al, 1996;Scharton-Kersten et al, 1997;Liesenfeld et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms of tissue cyst rupture and bradyzoite release in T. gondii have not yet been fully elucidated (Dzierszinski et al, 2004;Ibrahim et al, 2009). Once T. gondii infects humans and forms cysts during the chronic phase; encysted bradyzoites can rupture, reactivate into actively replicating and cytolytic tachyzoites, and cause symptomatic disease in immunocompromised individuals, such as people with HIV-AIDS or organ transplantation patients (Sullivan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%